Robotic transanal minimally invasive surgery – technical, oncological and patient outcomes from a single institution. (19th May 2020) - Baker, E. J.; Waters, P. S.; Peacock, O.; Narasimhan, V.; Larach, T.; McCormick, J.; Heriot, A. G.; Warrier, S.; Lynch, C.
Abstract: Aim: Robotic transanal minimally invasive surgery (R‐TAMIS) is gaining traction around the globe as an alternative to laparoscopic conventional TAMIS for local excision of benign and early malignant rectal lesions. The aim was to analyse patient and oncological outcomes of R‐TAMIS for consecutive cases in a single centre. Methods: A prospective analysis of consecutive R‐TAMIS procedures over a 12‐month period was performed. Data were collated from hospital databases and theatre registers. Results: Eleven patients (six men, five women), mean age 69.81 years (51−92 years), underwent R‐TAMIS over 12 months utilizing a da Vinci Xi platform. The mean lesion size was 36 mm (20–60 mm) with a mean distance from the anal verge of 7.5 cm (3–14 cm). Five lesions were posterior in anatomical location, four anterior, one right lateral and one left lateral. All procedures were performed in the lithotomy position using a GelPOINT Path Platform. Mean operative time was 64 min (40–100 min). Complete resection was achieved in 10/11 patients with two patients being upgraded to a diagnosis of adenocarcinoma. Nine patients were diagnosed with dysplastic lesions. Four patients had a false positive diagnosis of an invasive tumour on MRI. Six patients required suturing for full‐thickness resections. One patient had a postoperative bleed requiring repeat endoscopy and clipping. One patient (full‐thickness resection of T3 tumour) proceeded to a formal resection without difficulty with no residual disease (T0N0, 0/22). One patient with a fully resected T2 tumour is undergoing a surveillance protocol. The mean length of stay was 1 day with two patients having a length of stay of 2 days and one patient of 4 days. Conclusion: R‐TAMIS could potentially represent a safe novel approach for local resection of rectal lesions.